2020
DOI: 10.5194/hess-24-61-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting past flood events: the contribution of citizen science

Abstract: Information gathered on past flood events is essential for understanding and assessing flood hazards. In this study, we present how citizen science can help to retrieve this information, particularly in areas with scarce or no authoritative measurements of past events. The case study is located in Yeumbeul North (YN), Senegal, where flood impacts represent a growing concern for the local community. This area lacks authoritative records on flood extent and water depth as well as information on the chain of caus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
(57 reference statements)
0
22
0
2
Order By: Relevance
“…In the study, flood depths and extents were retrieved for multiple flood events (between 2005, 2009, 2012) based on personal recollections using two (independent) sets of community representatives. Sy et al (2020) observed a good agreement after comparing flood spatial extents derived with a communitybased approach and remotely sensed data. Given observed progress in the application of community-based data and the urgent need for understanding flood risk, especially in vulnerable regions, Assumpção et al (2018) and Sy et al (2020) have recommended exploring new alternatives in integrating such data into hydrodynamic models in data-scarce regions.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the study, flood depths and extents were retrieved for multiple flood events (between 2005, 2009, 2012) based on personal recollections using two (independent) sets of community representatives. Sy et al (2020) observed a good agreement after comparing flood spatial extents derived with a communitybased approach and remotely sensed data. Given observed progress in the application of community-based data and the urgent need for understanding flood risk, especially in vulnerable regions, Assumpção et al (2018) and Sy et al (2020) have recommended exploring new alternatives in integrating such data into hydrodynamic models in data-scarce regions.…”
Section: Introductionmentioning
confidence: 69%
“…Recent reviews by Assumpção et al (2018) and Sy et al (2019) showed that studies that utilize data, collected from affected communities, to reconstruct past flood scenario are increasing. Such an approach, using knowledge from affected communities, is particularly encouraged in data-scarce regions given their potential to provide low cost and sizeable data with good spatial and temporal coverage (Sy et al 2019(Sy et al , 2020Assumpção et al 2018). For example, several studies have reconstructed past floods using either water depths and velocity retrieved from texts, pictures and videos uploaded to social media platforms (see review by Assumpção et al 2018)) or flood duration derived using interviews (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, vulnerability indices have been identified to lack a stand-alone meaning outside a relative comparison of building vulnerability (Tarbotton et al, 2012;Dall'Osso and Dominey-Howes, 2013). This is a major limitation given the quality of information contained in the vulnerability index.…”
Section: Challenges and Gaps In Physical Vulnerability Indicators Andmentioning
confidence: 99%